A Lithium-ion Battery Using Partially Lithiated Graphite Anode and Amphi-redox LiMn2O4 Cathode. Issue 1 (December 2017) - Jeon, Yuju; Noh, Hyun; Song, Hyun-Kon
Abstract Delithiation followed by lithiation of Li+ -occupied (n-type) tetrahedral sites of cubic LiMn2 O4 spinel (LMO) at ~4  $${{\bf{V}}}_{{{\bf{Li}}{\boldsymbol{/}}{\bf{Li}}}^{{\boldsymbol{+}}}}$$ V Li / Li + (delivering ~100 mAh gLMO −1 ) has been used for energy storage by lithium ion batteries (LIBs). In this work, we utilized unoccupied (p-type) octahedral sites of LMO available for lithiation at ~3  $${{\bf{V}}}_{{{\bf{Li}}{\boldsymbol{/}}{\bf{Li}}}^{{\boldsymbol{+}}}}$$ V Li / Li + (delivering additional ~100 mAh gLMO −1 ) that have never been used for LIBs in full-cell configuration. The whole capacity ofamphi -redox LMO, including both oxidizable n-type and reducible p-type redox sites, at ~200 mAh gLMO −1 was realized by using the reactions both at 4 $${{\bf{V}}}_{{{\bf{Li}}{\boldsymbol{/}}{\bf{Li}}}^{{\boldsymbol{+}}}}$$ V Li / Li + and 3  $${{\bf{V}}}_{{{\bf{Li}}{\boldsymbol{/}}{\bf{Li}}}^{{\boldsymbol{+}}}}$$ V Li / Li + . Durable reversibility of the 3 V reaction was achieved by graphene-wrapping LMO nanoparticles (LMO@Gn). Prelithiated graphite (Lin C6, n < 1) was used as anodes to lithiate the unoccupied octahedral sites of LMO for the 3 V reaction.